Photocatalytic Degradation of Rhodamine B by C and N Codoped TiO2 Nanoparticles under Visible-Light Irradiation - Thuy Thi Thanh Le; Trinh Dinh Tran (Journal of Chemistry)
C and N codoped TiO2 nanoparticles were synthesized via a solvothermal method. The degradation of Rhodamine B by the photocatalyst C, N-TiO2 was investigated under visible-light irradiation generated by using a 36 W compact fluorescent lamp which is characterized by wavelengths from 400 to 650 nm. The structure and properties of the obtained photocatalyst have been systematically investigated using X-ray diffraction, TEM, UV-Vis, FT-IR, and BET techniques. The experimental results revealed that C, N codoped TiO2 nanoparticles were successfully synthesized, with an average diameter of 9.1 nm. C, N-TiO2 nanoparticles exhibited an energy band gap of 2.90 eV, which were lower than pristine TiO2 (3.34 eV), C-TiO2 (3.2 eV), and N-TiO2 (3.03 eV). The degradation of Rhodamine B by C, N-TiO2 indicated that, under visible-light irradiation, the optimal dose of the photocatalyst was 1.8 g/L, and the removal of Rhodamine B was almost complete after 3 hours of reaction. The photocatalytic degradation of Rhodamine B in the range of 5–100 mg/L showed that the process followed the first-order kinetics according to the Langmuir–Hinshelwood model. The highest apparent rate constant (0.0427 min−1) was obtained when the initial concentration of Rhodamine B was 5 mg/L, whereas the former decreased with the increase in the initial concentration of Rhodamine B. Moreover, C and N codoped TiO2 nanoparticles presented a high potential for recycling, which was characterized by a removal efficiency of more than 86% after three cycles.